Proceedings of the Ninth International Conference on Tangible, Embedded, and Embodied Interaction 2015
DOI: 10.1145/2677199.2680555
|View full text |Cite
|
Sign up to set email alerts
|

Using a Tangible Versus a Multi-touch Graphical User Interface to Support Data Exploration at a Museum Exhibit

Abstract: We describe a study comparing the behavior of museum visitors at an interactive exhibit that used physical versus virtual objects to explore a large scientific dataset. The exhibit visualized the distribution of phytoplankton in the world's oceans on a multi-touch table. In one version, visitors used physical rings to look at the type and proportion of phytoplankton in different areas of the oceans, and in the other version they used virtual rings. The findings suggest that the physical rings better afforded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 24 publications
(22 reference statements)
1
19
0
2
Order By: Relevance
“…For example, in the story of Cinderella 2000, snapping together the image of Cinderella's evil stepmother's face with the image of her house would play the audio clip of Cinderella's step mother yelling at Cinderella. An example of a similar interactive system in a museum exhibit is an installation in the Exploratorium in San Francisco that allows visitors to explore phytoplankton populations in the world's oceans [24]. The installation consists of a physical ring that functions as a digital magnifying glass placed on top of an interactive multi-touch tabletop.…”
Section: Tangible and Embodied Narrative Systemsmentioning
confidence: 99%
“…For example, in the story of Cinderella 2000, snapping together the image of Cinderella's evil stepmother's face with the image of her house would play the audio clip of Cinderella's step mother yelling at Cinderella. An example of a similar interactive system in a museum exhibit is an installation in the Exploratorium in San Francisco that allows visitors to explore phytoplankton populations in the world's oceans [24]. The installation consists of a physical ring that functions as a digital magnifying glass placed on top of an interactive multi-touch tabletop.…”
Section: Tangible and Embodied Narrative Systemsmentioning
confidence: 99%
“…Ma et al [14] compared tangible and graphical versions of an exhibit and found that while the tangible version attracted more visitors, there was not necessarily a difference in the visitors' experience with the exhibit. However, their exhibit utilized only three tangibles that needed to be shared among visitors.…”
Section: Tangible Interaction For Learningmentioning
confidence: 99%
“…One example is a museum exhibit that enables users to explore the distribution of oceanic phytoplankton using ring objects and a 55-inch custom-built table. Compared to a multi-touch interface, the tangible exhibit improved affordance, which attracted groups and invited further exploration [14]. Another example is G-nome surfer, which is a multi-touch tabletop interface that uses tangible objects as containers for generelated information.…”
Section: Related Workmentioning
confidence: 99%
“…TEI '16, February 14-17, 2016 analysis [17] to access data, perform calculations, adjust parameters and manipulate windows. Most systems only support mouse and keyboard interaction, although some post-WIMP (Windows, Icons, Menu, Point) setups use projections onto walls and tabletops [11,14,18,20,21]. This paper outlines the design of a tabletop TUI for interactive data visualization, and it makes two main contributions.…”
Section: Introductionmentioning
confidence: 99%